Influence of aluminum on structural properties of iron-polyphosphate glasses - Stoch, Paweł; Goj, Paweł; Ciecińska, Małgorzata; Jeleń, Piotr; Błachowski, Artur; Stoch, Agata; Krakowiak, Ireneusz (Ceramics international, 2020)
Phosphate glasses are materials that can be used in many technological fields. Their possible application may be limited due to the existence of easily hydrated P–O–P bonds. Addition of Al2O3, Fe2O3 strongly improves the durability of the glasses. The subject of the studies are iron-polyphosphate glasses in which iron is gradually substituted by aluminum. The glasses have been tested using FT-IR, Raman, and Mössbauer spectroscopies. The obtained experimental results were compared to the theoretical prediction of the glass network structure by ab initio molecular dynamics. It was shown that the substitution leads to an increase in the glass network polymerization. The glass network is inhomogenous with Al/Fe-rich and poor regions. In the poor regions, Al/Fe cations are glass network modifiers whereas in the rich they can be the glass network formers. Mayer's Bond Order analysis was used to describe bonding mechanisms in the glasses. The existence of the mix-valence iron atoms has been postulated.